Development of Google Sites-Based Interactive Learning Media for Handball Instruction in Physical Education (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2026)
The rapid advancement of technology has encouraged innovation in educational practices through digital learning media. However, studies specifically developing and validating Google Sites-based interactive media for handball instruction in Physical Education, Sports, and Health learning (PJOK) at the junior high school level remain limited. Therefore, the novelty of this study lies in the systematic development and expert validation of an interactive Google Sites-based learning medium designed specifically for handball instruction to support active and problem-based learning. This study aimed to develop and assess the validity of the media implemented at a junior high school in Padang. The research employed a Research and Development approach using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. Needs analysis was conducted through classroom observations and teacher interviews. The product was developed using Google Sites by integrating text, images, videos, and evaluation components. Validation was carried out by media, language, and subject-matter experts using Likert-scale instruments, while the data were analyzed through percentage calculations. The results showed an overall validity score of 90.67%, categorized as very valid. These findings imply that validated web-based media can enhance student engagement and support more interactive PJOK learning.